(untitled) (American Journal of Interdisciplinary Research and Innovation, 2024)
In tropical climate, restricting convective gain while allowing cross ventilation creates paradoxical difficulty regarding indoor thermal comfort. Changing global climate gives new dimensions to the scenario results in subsequent pressure on increasing energy demand towards thermal comfort. Passive techniques can be a good way to dealt with the problem. However, occupants’ thermal perception may vary from person to person for a definite indoor environmental setup. Perception of subjective thermal comfort is crucial for human health and wellbeing which in turns effects performance. In the current study evaluation of subjective thermal performance regarding improved indoor thermal comfort has been studied for three different local window screening: i) plastic bottle with its wider face towards wind direction, ii) plastic bottle with its narrower face towards wind direction and iii) perforated bamboo screen. Six subjects: four female and two male (ages between 22-24), have been investigated for 30mins. in an experimental simulation chamber for three consecutive days. Questionnaire regarding thermal sensation and perception has been prepared to collect subjective response at 10mins. interval. From the experiment it is seen that subjective responses varies for different window screenings as well as for a specific indoor thermal condition created with definite screening. Subjects find the indoor environment comfortable for screening with plastic bottle with its wider face towards wind direction compared to other two. Bamboo screening has comparatively better performance than the screening plastic bottle with its narrower face towards wind direction. The current analysis only considers the thermal sensation of the subject and further extension of study considering factors like the subject’s site-specific thermal sensation and other psychological effects can contribute towards improving indoor thermal comfort in tropics towards human health and wellbeing.